2011
DOI: 10.1002/jcp.22486
|View full text |Cite
|
Sign up to set email alerts
|

FTS (fused toes homolog) a novel oncoprotein involved in uterine cervical carcinogenesis and a potential diagnostic marker for cervical cancer

Abstract: The high incidence and fatality rate of uterine cervical cancer warrant effective diagnostic and therapeutic target identification for this disease. Here, we have found a novel oncoprotein FTS (Fused Toes Homolog), which is involved in cervical cancer pathogenesis. Immunohistochemical analysis of human cervical biopsy samples revealed that the expression of FTS is absent in normal cervical epithelium but progressively overexpressed in human cervical intraneoplastic lesions (CIN-I to CIN-III), this characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Based on data from the Cancer Genome Atlas, homologous deletion of AKTIP occurs in multiple cancer lineages including breast (2%), ovary (0.9%), and prostate (1%), consistent with a tumor-suppressor role. However, the functional role of AKTIP could be tumor type-specific, since it has been proposed as a putative oncoprotein in cervical cancer but a tumor suppressor in ovarian cancer (Cinghu et al 2011;Notaridou et al 2011). INHBA encodes inhibin beta A, a subunit of both the activin and inhibin receptors of the transforming growth factor (TGF-beta) superfamily (Risbridger et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Based on data from the Cancer Genome Atlas, homologous deletion of AKTIP occurs in multiple cancer lineages including breast (2%), ovary (0.9%), and prostate (1%), consistent with a tumor-suppressor role. However, the functional role of AKTIP could be tumor type-specific, since it has been proposed as a putative oncoprotein in cervical cancer but a tumor suppressor in ovarian cancer (Cinghu et al 2011;Notaridou et al 2011). INHBA encodes inhibin beta A, a subunit of both the activin and inhibin receptors of the transforming growth factor (TGF-beta) superfamily (Risbridger et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…FTS expression is undetectable in normal epithelial cervical cells. Its expression positively correlates with the stage and grade of cervical cancer [45]. EGF treatment increases the phosphorylation of EGFR and ERK, leading to the accumulation of ATF2 in the nucleus [46].…”
Section: Oncogenes and Emt In Cervical Cancermentioning
confidence: 99%
“…FTS (Fused Toes Homolog) is an oncogene involved in cervical cancer pathogenesis [45]. FTS expression is undetectable in normal epithelial cervical cells.…”
Section: Oncogenes and Emt In Cervical Cancermentioning
confidence: 99%
“…It was found to interact with PKB and PDK when overexpressed and also promoted apoptosis in T-lymphocytes when treated with glucocorticoids [10]. Previous studies from our lab demonstrated a progressive expression of FTS with the progressive grades if cervical intraepithelial neoplasia (CIN) [11]. Disruption of FTS expression led to the shutdown of key elemental characteristics of the cervical cancer cells and resulted in apoptosis.…”
Section: Introductionmentioning
confidence: 92%